Performans reproduksi induk babi yang di pelihara secara intensif di Kelurahan Kambajawa Kabupaten Sumba Timur - Alexander Kaka (Faculty of Animal Science, Universitas Brawijaya, 2018)
The purpose of this research is to know the performance of sows reproduction intensively in Kambajawa sub-district, East Sumba regency. The study was conducted from January until March 2017 and this research is a survey method with a direct interview to 200 respondents as a population and 196 sows. The data were analyzed by descriptive statistic approach depicted on frequency table for each indicator or dimension. The measured variables were estrus time; estrus cycle; litter size; wean quantity; and mortality rate. Based on this study, it is known that the reproductive performance of the sows maintained intensively was categorized well. Thus, it can be concluded that the reproductive performance of sows in Kambajawa district that is, estrus duration 4.21±1.10 days, estrus cycle 21.15±1.64 days, litter size 8.50±1.39 and 39.71% of mortality.